TINJAUAN YURIDIS TERHADAP PAJAK DAERAH DAN RETRIBUSI DAERAH STUDI PELAKSANAAN DI UNIT PELAYANAN PAJAK DAERAH SAMSAT KOTA BINJAI - Ria Sintha Devi; Novi Juli Rosani Zulkarnaen; Rani Ika Pratiwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2021)
This study aims to determine the implementation of regulations along with the impacts and obstacles experienced by the UPPD Samsat Binjai regarding regional taxes and regional levies in the fields of Motor Vehicle Taxes, Transfer Fees for Motorized Vehicles and Surface Water Taxes and their relationship with the Civil Code (Burgerlijk Wetboek). ). The researcher uses normative and juridical empirical/sociological research, empirical juridical implementation studies in the form of interviews, observations and valid data from the Regional Tax Service Unit of Samsat Binjai. The key instrument in this research is the researcher himself and this research uses qualitative descriptive data analysis techniques. The final result of this study is that the implementation of the regulation has been optimal even though in the field it is not always smooth but still on the regulations that are set and are closely related to the Civil Code because tax law takes the basics of tax collection and so on based on article 1233 of the Criminal Code concerning engagement (verbintenis).